2014
DOI: 10.1016/j.virol.2014.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Host restriction of murine gammaherpesvirus 68 replication by human APOBEC3 cytidine deaminases but not murine APOBEC3

Abstract: Humans encode seven APOBEC3 (A3A-A3H) cytidine deaminase proteins that differ in their expression profiles, preferred nucleotide recognition sequence and capacity for restriction of RNA and DNA viruses. We identified APOBEC3 hotspots in numerous herpesvirus genomes. To determine the impact of host APOBEC3 on herpesvirus biology in vivo, we examined whether murine APOBEC3 (mA3) restricts murine gammaherpesvirus 68 (MHV68). Viral replication was impaired by several human APOBEC3 proteins, but not mA3, upon trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 76 publications
2
28
1
Order By: Relevance
“…A role for the vUNG in countering AID restriction of gammaherpesvirus pathogenesis has not been studied. We recently reported that MHV68 replication is restricted by several host antiviral APO-BEC3 cytidine deaminases (44). However, we did not observe an enhanced restriction by the most restrictive APOBEC3, APOBEC3A, in the absence of the viral UNG (data not shown).…”
Section: Discussioncontrasting
confidence: 57%
“…A role for the vUNG in countering AID restriction of gammaherpesvirus pathogenesis has not been studied. We recently reported that MHV68 replication is restricted by several host antiviral APO-BEC3 cytidine deaminases (44). However, we did not observe an enhanced restriction by the most restrictive APOBEC3, APOBEC3A, in the absence of the viral UNG (data not shown).…”
Section: Discussioncontrasting
confidence: 57%
“…9C and D), it is possible that inhibition of papillomaviruses is an APOBEC3 function that developed late during vertebrate evolution. In fact, mA3 was also found to have no impact on murine gammaherpesvirus 68, another DNA virus (66). We speculate that other type I interferon-responsive proteins may further augment the antiviral effect in early MmuPV1 infection in mice (53,67,68).…”
Section: Discussionmentioning
confidence: 83%
“…MHV68 (10 3 PFU; WUMS strain) was intranasally inoculated into mice. The mice were sacrificed at 7 and 16 dpi for acute-and latent-infection analysis, respectively (34). Plaque assays were conducted to measure the virus titers during acute infection in the lungs.…”
Section: Mice A3ko A3amentioning
confidence: 99%
“…Evidence of APOBEC3A-, 3C-, and 3G-mediated editing of herpes simplex virus 1 (HSV-1) was detected when these factors were overexpressed in cultured cells, and HSV-1 and Epstein-Barr virus (EBV) showed signs of cytidine deamination in buccal swabs or immortalized cell lines, respectively (30). Moreover, a recent study showed that several human APOBEC3s, including APOBEC3A, inhibited replication of murine gammaherpesvirus 68 (MHV68) when the viral genome was transfected into cultured cells but not when it was introduced by infection (34). However, APOBEC3 knockout (A3KO) and wild-type (WT) mice were equally resistant to infection by this virus (34).…”
mentioning
confidence: 99%
See 1 more Smart Citation